Neutrophil-Lymphocyte Ratio in Patients with Ischemic Stroke (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The objects of the study were 32 patients with acute ischemic cerebral circulatory disorders, aged 52 to 65 years (the average age was 58.3±2 years), in whom clinical (systemic hemodynamic and respiratory indicators, neurological status), instrumental (ECG, chest X-ray, MSCT examination of the brain) were analyzed) and laboratory data (leucoformula, ISNL). Comparison of clinical and laboratory parameters was carried out in three stages: the first stage - upon admission, the second stage: – the 3rd day, the third stage - the 7th day of intensive care. It has been established that a high rate of SNL is a reliable indicator of the clinical deterioration of patients and a predictor of an unfavorable outcome of critical conditions caused by ONMC.